1993
DOI: 10.1152/jappl.1993.74.1.333
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of cigarette smoke on breathing is attenuated by chronic smoking in rats

Abstract: To determine whether the irritant effect of cigarette smoke on breathing was affected by chronic exposure to smoke, two groups of sixteen young male Sprague-Dawley rats were exposed daily to fresh cigarette smoke (treated group) or air (control group) for 4-8 wk. Acute ventilatory response to cigarette smoke (50% concn, 6 ml volume) inhaled via a tracheal cannula was then studied under anesthesia and compared between the two groups. Inhalation of either cigarette smoke or gas phase smoke induced an immediate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
1

Year Published

1995
1995
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…We examined the effects of chronically exposing young guinea pigs from 1 to 6 wk of life to sidestream tobacco smoke (the surrogate for ETS) on the local axon reflex and found that their isolated lungs showed a smaller increase in lung resistance (RL) in response to capsaicin injected in the pulmonary circulation than the filtered air-exposed controls did (18). These findings, like those by Swanny et al (33), are consistent with the notion that chronic exposure to environmental or mainstream tobacco smoke can result in a blunted responsiveness of some components of the C-fiber reflex.…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…We examined the effects of chronically exposing young guinea pigs from 1 to 6 wk of life to sidestream tobacco smoke (the surrogate for ETS) on the local axon reflex and found that their isolated lungs showed a smaller increase in lung resistance (RL) in response to capsaicin injected in the pulmonary circulation than the filtered air-exposed controls did (18). These findings, like those by Swanny et al (33), are consistent with the notion that chronic exposure to environmental or mainstream tobacco smoke can result in a blunted responsiveness of some components of the C-fiber reflex.…”
mentioning
confidence: 53%
“…Karlsson et al (20) reported that chronic exposure to mainstream tobacco smoke (1 h twice daily for 2 wk) enhanced coughing induced by nebulized citric acid or capsaicin, suggesting that prolonged exposure to mainstream smoke may augment C-fiber activity or at least reflex function. On the other hand, Swanny et al (33) showed that chronic exposure to mainstream tobacco smoke (over 4-8 wk) attenuated the reflex apnea and tachypnea evoked by acutely inhaled mainstream tobacco smoke. These findings suggest that C-fiber responsiveness, at least to acute inhalation of mainstream tobacco smoke, rather than being augmented, may be blunted by continuous exposure to mainstream tobacco smoke (33).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Receptor responses are larger when the nicotine but not the particulate content is higher, and nicotine receptor antagonists prevent the effect of cigarette smoke on vagal pulmonary receptors (Lee et al 1989;Kou & Lee, 1990). There are data suggesting that in addition to the effects of inhaled nicotine on the pulmonary vagal sensory receptors, absorbed nicotine may excite the vagal receptors and also the peripheral and central chemoreceptors (Hartiala, Mapp, Mitchell, Shields & Gold, 1984;Swanny, Morton & Lee, 1993). Intravertebral injections of donor blood collected during inhaled smoke from one cigarette has been shown to increase respiration in dogs, approximately 60 s after the infusion (Hartiala, Mapp, Mitchell & Gold, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Intravertebral injections of donor blood collected during inhaled smoke from one cigarette has been shown to increase respiration in dogs, approximately 60 s after the infusion (Hartiala, Mapp, Mitchell & Gold, 1985). Lee and colleagues have shown that inhalation of cigarette smoke can produce a delayed tachypnoea (5-15 breaths after smoke) that remains after vagotomy (Swanny et at. 1993).…”
Section: Cigarette-' (English Ovals King Size; Federal Tradementioning
confidence: 99%